Allometric equations for the aboveground biomass of five tree species in China using the generalized method of moments - Jia Wang; Longyu Zhang; Zhongke Feng (The Forestry Chronicle, 2018)
Allometric equations are extensively used for estimating aboveground biomass. Although they have been developed for many tree species, there are many species for which no such equations exist. Destructive sampling is necessary to obtain data for fitting such equations. Standard fitting techniques work best with large sample sizes, however, such sizes may not be feasible in some conditions. In this paper, we propose using the generalized method of moments (GMM) as a replacement for the more usual fitting technique of logarithmic transformation and ordinary least squares regression. This technique is illustrated using 78 trees from five species in Gansu Province, China. Our results show that the allometric equations developed using the GMM provided more accurate biomass estimates than those developed using the standard fitting approach, and were also able to overcome the problem of heteroscedasticity often associated with fitting biomass equations with small samples.